A European multicentre evaluation of detection and typing methods for human enteroviruses and parechoviruses using RNA transcripts. Issue 8 (17th January 2020) - Hayes, A.; Nguyen, D.; Andersson, M.; Antón, A.; Bailly, J.‐L.; Beard, S.; Benschop, K. S. M.; Berginc, N.; Blomqvist, S.; Cunningham, E.; Davis, D.; Dembinski, J. L.; et al.
Abstract: Polymerase chain reaction (PCR) detection has become the gold standard for diagnosis and typing of enterovirus (EV) and human parechovirus (HPeV) infections. Its effectiveness depends critically on using the appropriate sample types and high assay sensitivity as viral loads in cerebrospinal fluid samples from meningitis and sepsis clinical presentation can be extremely low. This study evaluated the sensitivity and specificity of currently used commercial and in‐house diagnostic and typing assays. Accurately quantified RNA transcript controls were distributed to 27 diagnostic and 12 reference laboratories in 17 European countries for blinded testing. Transcripts represented the four human EV species (EV‐A71, echovirus 30, coxsackie A virus 21, and EV‐D68), HPeV3, and specificity controls. Reported results from 48 in‐house and 15 commercial assays showed 98% detection frequencies of high copy (1000 RNA copies/5 µL) transcripts. In‐house assays showed significantly greater detection frequencies of the low copy (10 copies/5 µL) EV and HPeV transcripts (81% and 86%, respectively) compared with commercial assays (56%, 50%; P = 7 × 10 −5 ). EV‐specific PCRs showed low cross‐reactivity with human rhinovirus C (3 of 42 tests) and infrequent positivity in the negative control (2 of 63 tests). Most or all high copy EV and HPeV controls were successfully typed (88%, 100%) by reference laboratories, but showed reduced effectiveness for low copy controls (41%, 67%). Stabilized RNA transcripts provide an effective, logistically simple and inexpensive reagent for evaluation of diagnostic assay performance. The study provides reassurance of the performance of the many in‐house assay formats used across Europe. However, it identified often substantially reduced sensitivities of commercial assays often used as point‐of‐care tests.